Identification of Niche Conditions Supporting Short-term Culture of Spermatogonial Stem Cells Derived from Porcine Neonatal Testis - Min Hee Park; Ji Eun Park; Min Seong Kim; Kwon Young Lee; Jung Im Yun; Jung Hoon Choi; Eunsong Lee; Seung Tae Lee (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Despite that porcine spermatogonial stem cells (pSSCs) have been regarded as a practical tool for preserving eternally genetic backgrounds derived from pigs with high performance in the economic traits or phenotypes of specific human diseases, there were no reports about precise definition of niche conditions promoting proliferation and maintenance of pSSCs. Accordingly, we tried to determine niche conditions supporting proliferation and maintenance of undifferentiated pSSCs for short-term. For these, undifferentiated pSSCs were progressively cultured in different composition of culture medium, seeding density of pSSCs, type of feeder cells and concentration of growth factors, and then total number of and alkaline phosphatase (AP) activity of pSSCs were investigated at post-6 day culture. As the results, the culture of 4 × 105 pSSCs on mitotically in activated 2 × 105 STO cells in the mouse embryonic stem cell culture medium (mESCCM) supplemented with 30 ng/ml glial cell line-derived neurotrophic factor (GDNF) was identified as the best niche condition supporting effectively the short-term maintenance of undifferentiated pSSCs. Moreover, the optimized short-term culture system will be a basis for developing long-term culture system of pSSCs in the following researches